2012
DOI: 10.1007/s00441-012-1397-5
|View full text |Cite
|
Sign up to set email alerts
|

Are TRP channels involved in sperm development and function?

Abstract: Spermatozoa must translate information from their environment and the egg to achieve fertilization in sexually reproducing animals. These tasks require decoding a variety of signals in the form of intracellular Ca(2+) changes. As TRP channels constitute a large family of versatile multi-signal transducers, they are interesting subjects in which to explore their possible participation in sperm function. Here, we review the evidence for their presence and involvement in sperm motility, maturation, and the acroso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 138 publications
2
29
0
Order By: Relevance
“…Here, we adopted a pharmacological approach to characterize the exact function of TRPC3, one member of the TRPC family, in sperm motility and capacitation. Consistent with previous findings [26,28], we confirmed that TRPC3 is located on the flagellum; however, we showed that TRPC3 only localizes to the mid-piece of sperm. These inconsistent results may be due to the differences in the sensitivity and specificity of the antibodies used in each study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Here, we adopted a pharmacological approach to characterize the exact function of TRPC3, one member of the TRPC family, in sperm motility and capacitation. Consistent with previous findings [26,28], we confirmed that TRPC3 is located on the flagellum; however, we showed that TRPC3 only localizes to the mid-piece of sperm. These inconsistent results may be due to the differences in the sensitivity and specificity of the antibodies used in each study.…”
Section: Discussionsupporting
confidence: 92%
“…The functions of multiple types of Ca 2+ channels in sperm have also been documented [19]. Previous studies using the TRPC inhibitor SKF96365 demonstrated that the members of the TRPC family play an important role in sperm motility [26][27][28]. Here, we adopted a pharmacological approach to characterize the exact function of TRPC3, one member of the TRPC family, in sperm motility and capacitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is accepted that the main targets of Ca 2ϩ are specific calcium-binding proteins such as synaptotagmin (8,9), even if Ca 2ϩ also activates calmodulin-dependent enzymes such as PI3K, whose inactivation blocks the AR (10). Numerous agonist-dependent actors involved in [Ca 2ϩ ] increase have been characterized, including Ca 2ϩ influx through activation of voltage-dependent calcium channels and store-operated channels and calcium release from the acrosome itself through activation of PLC␦4 and the inositol 1,4,5-trisphosphate receptor (2,(11)(12)(13). Contrary to neuronal exocytosis where [Ca 2ϩ ] increase is followed within milliseconds by degranulation, sperm granule exocytosis spreads over 30 min in the presence of the agonists.…”
mentioning
confidence: 99%
“…Evidence indicates internal Ca 2+ stores (i.e., the acrosome) participate releasing Ca 2+ through the IP3 receptor, the second type of Ca 2+ channel involved in the AR, which is activated as a consequence of IP3 production during the AR Florman et al 2008 ;Mayorga et al 2007 ;Publicover et al 2007 (Costello et al 2009 ;Darszon et al 2012 ).…”
Section: The Acrosome Reactionmentioning
confidence: 99%